EVALUASI PROGRAM PEMANENAN AIR HUJAN (RAIN WATER HARVESTING) BADAN LINGKUNGAN HIDUP KOTA SEMARANG - Debby Rinata Abadi; Kismartini Kismartini; Sundarso Sundarso (Departemen Administrasi Publik, Universitas Diponegoro, 2018)
The formulation of climate change impacts in Semarang produced five major issues: flooding, tidal flood, landslides, drought and outbreaks of infectious diseases. Rain Water Harvesting Program implemented by Regulation of the Minister of Environment No. 12 in 2009 was an attempt by Semarang government for adaptation to climate change. This evaluation aims to determine the results of the implementation and the factors that affect the implementation of the program. The results can be seen through the implementation of an evaluation process based on the Model Evaluation System Analysis in inputs, processes and outputs Based on Suitability Model by David C. Korten factors that support and hinder namely compatibility between programs with beneficiaries, the fit between programs by implementing organizations and the fit between user groups with the implementing organization. Based on the existing obstacles in the implementation of the Program Harvesting Rain Water Environment Agency of Semarang, the authors give a recommendation either: (1) changes in socialization patterns, (2) not only focus on physical development but the socialization benefits of using rainwater, (3) improving access to information for community, (4) make scientific criteria for target groups, (5) integrated with IMB licensing requirements.